MAKNA SATIRE KESENIAN SENJANG MUSI BANYUASIN SUMATERA SELATAN DALAM PERSPEKTIF SEMIOTIKA KOMUNIKASI - Mutia Tanseba Andani; Ronald Candra (Jurnal Prodi Ilmu Komunikasi, 2023)
This research attempts to describe the implied meaning of satire in the artistic poetry of the Musi Banyuasin Community, South Sumatra. This senjang art poetry uses local regional language in the form of rhymes, sung by one or two poets. The satire used varies from persuasion, criticism, or satire, making it interesting to study further. This research uses qualitative methods with Roland Barthes' communication semiotic analysis. Semiotics will recognize signs and meanings in poetry, with a theoretical review of satire and communication semiotics. The formulation of the problem in this research is what is the meaning of satire in contemporary art from a communication semiotics perspective? This research aims to find out and describe the meaning of satire contained in the senjang poems. The meaning of satire according to Roland Barthes' communication semiotics includes denotation (true meaning) and connotation (double meaning), which are termed signifiers and signifieds. So the conclusion from this research is that sengjang art is also sung in the form of satire full of meaning, and the implied meaning is more political.